2008
DOI: 10.1007/s10549-008-0243-7
|View full text |Cite
|
Sign up to set email alerts
|

Extensive expression of craniofacial related homeobox genes in canine mammary sarcomas

Abstract: The global gene expression in three types of canine mammary tumors: carcinoma, fibrosarcoma and osteosarcoma were investigated by Affymetrix gene array technology. Unsupervised clustering analysis revealed a close clustering of the respective tumor types, with fibrosarcomas clustering close to the osteosarcomas and the carcinomas clustering closer to non-malignant mammary tissues (NMTs). A number of epithelial markers were expressed in both carcinomas and NMTs, whereas the sarcomas expressed genes related to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The massive downregulation of a number of homeobox and zinc finger genes during uterine infection is intriguing. Homeobox transcription factors have been widely implicated mainly in embryonal development and in cancer [18] , [51] and the data presented here thus expand their repertoire of functions by implicating them in bacterial disease. Although we cannot with certainty explain why the homeobox genes are downregulated during disease, we may speculate that homeobox genes, during homeostatic conditions, have a role in suppressing pro-inflammatory pathways, and that downregulated expression of homeobox genes may unleash inflammatory cascades.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The massive downregulation of a number of homeobox and zinc finger genes during uterine infection is intriguing. Homeobox transcription factors have been widely implicated mainly in embryonal development and in cancer [18] , [51] and the data presented here thus expand their repertoire of functions by implicating them in bacterial disease. Although we cannot with certainty explain why the homeobox genes are downregulated during disease, we may speculate that homeobox genes, during homeostatic conditions, have a role in suppressing pro-inflammatory pathways, and that downregulated expression of homeobox genes may unleash inflammatory cascades.…”
Section: Discussionmentioning
confidence: 61%
“…Total RNA was prepared from cross-sections of frozen uterine tissue samples, using Nucleospin RNA II (Macherey-Nagel, Düren, Germany). Affymetrix gene chip microarray analysis was performed using the Canine Genome 2.0 Array, as described [18] . The raw data were normalized using the robust multi-array average (RMA) [19] background-adjusted, normalized and log-transformed summarized values.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the majority of CMSs were diagnosed in large-breed dogs. To date, only one study has demonstrated that CMSs were common in medium- and large-breed dogs [11]. In our opinion, the fact that CMSs are most frequently observed in large-breed dogs could be attributed to the high popularity of those breeds in Poland.…”
Section: Discussionmentioning
confidence: 84%
“…Using paired-end whole genome sequencing, whole-exome sequencing and RNA-seq, Liu et al (2014) showed that while mammary carcinomas have extensive genomic aberrations, complex tumours contain mostly epigenomic aberrations (Liu et al, 2014). A further study using microarray analysis separated gene expression of canine mammary carcinomas from sarcomas and identified homeobox genes as overexpressed in the latter (Wensman et al, 2009). Such studies may have diagnostic potential in particularly undifferentiated tumours and further work may relate these gene signatures to prognosis or to key pathways for targeted chemotherapy.…”
Section: Mammary Tumoursmentioning
confidence: 99%